Analysis of correlation between the indicators of myocardial dyssynchrony and structural and functional parameters of myocardium - Асоян, Ірина Миколаївна (ScienceRise: Medical Science, 2016)
Aim. To reveal the correlations between the values of dyssynchrony indicators and echocardiographic indices of myocardium state in patients with chronic heart failure of ischemic genesis, diabetes mellitus type 2 and heart dyssynchrony. Methods. The research included 61 patients with chronic heart failure of ischemic etiology, diabetes mellitus type 2 and heart dyssynchrony. The structural-functional features of myocardium and mechanical types of dyssynchrony were studied using echocardiography in М- and B- modes, impulse and permanent-wave Dopplerechocardiography, spectral tissue Dopplerography. Electric dyssynchrony was studied using electrocardiography. Results. Progressing of intraventricular (increase of Ts and Ts-SD) and atrioventricular dyssynchrony (decrease of LVFT) favor the increase of final systolic and diastolic sizes and volumes, growth of mass and index of the left ventricle myocardium mass and synchronous thinning of the left ventricle wall. The strengthening of myocardium dyssynchrony favors the growth of the mean parameters that characterize the heart work: striking volume, striking index, minute volume and heart index. The increase of Ts and Ts-SD indices causes the decrease of discharge fraction and the degree of shortening of the front-back size into systole that is the pumping function of heart worsens. Conclusions. The heart dyssynchrony has a negative influence on the process of heart remodeling, the load on the left ventricle increases and the pumping function decreases that favor the progressing of chronic heart failure in patients with diabetes mellitus type 2